Risk of Hearing Impairment due to Noise Exposure among Textile Industry Workers at PT X in 2025 - Farhana Syahrotun Nisa Suratna; Maria Paskanita; Sumardiyono Sumardiyono; Seviana Rinawati; Tutug Bolet Atmojo; Lusi Ismayeti; Bekti Utomo; Warda Yussy Rha; Jordan Syah Gustav (Miracle Journal of Public Health, 2025)
Occupational noise is one of the main preventable hazards that can seriously affect workers' health and productivity, causing noise-induced hearing loss. This study aims to analyze the relationship between noise exposure, age, and length of service with the level of hearing loss among workers in the textile weaving industry at PT X. This analytical observational study with a cross-sectional design was conducted on 30 workers in the textile weaving industry in Surakarta using purposive sampling techniques. Data were obtained through noise intensity measurements and audiometric examinations. Bivariate analysis was performed using the Spearman Rank test with a significance level of 0.05. The results showed that the average noise level at the workplace reached 90.78 dB, with the highest exposure in Room 5 Ring Line C at 104.78 dB. The correlation test showed a significant relationship between age (r= 0.411; p=0.024) and length of service (r=0.400; p=0.029) with the left ear hearing threshold value, while noise intensity was not significantly related. This indicates that individual factors and job characteristics such as age and length of service play a more dominant role in hearing loss than variations in workplace noise levels. It is concluded that there is a significant relationship between age and length of service and a decrease in the left ear hearing threshold of workers.